Legal Support for the Development and Use of Municipal Information Systems - S. E. Channov; R. V. Amelin (Сибирское юридическое обозрение)
The paper deals with the current issues of development and use of municipal information systems, and proposes their legal solutions. In particular, it is noted that federal legislation lacks a precise definition of a municipal information system. The analysis of regional and municipal lawmaking allows us to identify several attributes of municipal information systems: development or acquisition of the system by a decision of a local governing body; the powers of local governing bodies to implement the systems; full or partial financing from the local budget. In this regard, the Federal Law “On Information, Information Technologies and Information Protection” proposes to define a municipal information system as an information system created or acquired through a decision of a local governing body at the expense of the local budget and designed to solve the issues that are in jurisdiction of municipalities. The current municipal information systems can be divided into two groups: specialized information system complying with federal laws and general information systems designed to support the functioning of local governing bodies or municipal enterprises and institutions. At the same time, general municipal information systems of different municipal entities are rarely integrated. Therefore, when it is necessary, it becomes impossible or very difficult. This problem is mainly of organizational and technical nature. However, it is also a result of collisions and gaps in the regulatory framework of municipal information systems. To solve them, it seems necessary, firstly, to state in article 13 of the Federal Law “On Information, Information Technologies and Information Protection” the possibility to define the specifics of legal regulation of municipal information systems not only by legislative, but also bylaws on local selfgoverning; secondly, to indicate in the Federal Law “On General Organizational Principles of Local Self- Governing in the Russian Federation” the possibility of the subjects of the Russian Federation to be involved in lawmaking in municipal information systems.